2019
DOI: 10.1371/journal.pone.0217836
|View full text |Cite
|
Sign up to set email alerts
|

Study on knowledge about associated factors of Tuberculosis (TB) and TB/HIV co-infection among young adults in two districts of South Africa

Abstract: South Africa ranks third among 22 high burden countries in the world. TB which remains a leading cause of death causes one in five adult deaths in South Africa. An in-depth understanding of knowledge, attitudes and practices of young people towards TB is required to implement meaningful interventions. We analysed young men and women (18–24 years)’s TB knowledge including TB/HIV coinfections, testing rates and factors associated with them. A cross sectional cluster-based household survey was conducted in two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
3
14
0
2
Order By: Relevance
“…Data were collected through a household survey. The detailed study methods were previously reported elsewhere [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected through a household survey. The detailed study methods were previously reported elsewhere [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…TB knowledge was assessed using eight questions that covered transmission, treatment and HIV/co-infection. Answering at least six questions was judged as knowledgeable of TB [ 25 ]. Four questions were used to judge a participant’s TB stigma through asking community attitudes towards people living with TB.…”
Section: Methodsmentioning
confidence: 99%
“…The sampling design used was multi-stage cluster sampling. The methodology for this study has been described elsewhere [6]. The only one district from Mpumalanga province (Nkangala district) was purposively selected while one district from Eastern Cape province (OR Tambo district) was randomly selected from 4 districts for inclusion in the study.…”
Section: Design and Settingmentioning
confidence: 99%
“…The individual responses for each participant were added and scored. We set the level of positive or accepting attitudes towards people living with HIV (PLWH) at 7 [6]. Being guided by the notion that community attitudes more broadly influence individual attitudes and also given that the study was conducted to enable an understanding of community views ahead of a community-wide programme of HIV testing, we assessed community HIV testing attitudes.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…South Africa is among the world´s most affected with TB/HIV co-infection contributing to an estimated 20% of the global burden of TB/HIV co-infections [ 15 ]. This has created a scenario where a large proportion of TB/HIV co-infected individuals in South Africa require concurrent treatment for TB and HIV/AIDS [ 16 ].…”
Section: Introductionmentioning
confidence: 99%